RISK FACTORS FOR THE INCIDENT OF PREECLAMPSIA IN THE DELIVERY ROOM OF SOEDONO MADIUN GENERAL HOSPITAL - Eka Wahyuni Wijayanti; Dewi Rachmawati; Sri Mugianti (Jurnal SMART Keperawatan, 2024)
Preeclampsia is a health problem in pregnant women that needs special attention because the exact cause is still unknown, and can cause death in the mother and fetus. The purpose of this study was to determine the risk factors for the incidence of preeclampsia in pregnant women in the Maternity Room of RSUD dr. Soedono Madiun. The research design used was descriptive quantitative method and accidental sampling technique. Data collection was carried out on 7 February-16 March 2024. The research instrument used was an interview sheet. The data analysis used is descriptive analysis. The results of this study indicate that the risk factors for preeclampsia are due to hypertension (94%), ANC (antenatal care) visits (90%), age (73%), obesity (45%), pregnancy distance (30%), parity (24%), diabetes mellitus (9%), asthma attacks (9%) and anaemia (3%), twin pregnancy (0%). Based on the risk factors for preeclampsia, the dominant risk factor for hypertension was 94%. This is because the average mother has a history of hypertension before pregnancy and recurrence after pregnancy so that it hinders the delivery process. Pregnant women must continue to maintain health during pregnancy by carrying out routine pregnancy checks in a timely manner and awareness of the risk of pregnancy preeclampsia that occurs.